Adverse drug reaction patterns of first-line anti-tubercular drugs among saharia tuberculosis patients: An observational study in particularly vulnerable tribal group of Madhya Pradesh, India - Prashant Mishra; Jyothi Bhat; Rajiv Yadav; Ravendra Kumar Sharma; Vikas Gangadhar Rao (Indian Journal of Public Health, 2023)
The Saharia tribe of Madhya Pradesh has a very high tuberculosis (TB) burden. However, there is no report of adverse drug reaction (ADR) available in patients receiving anti-TB chemotherapy in the community. Reporting and monitoring of ADRs among TB patients is still rare in marginalized communities. An observational prospective study was performed from November 2019 to June 2020 to assess the patterns of ADRs in 250 Saharia TB patients, who were prescribed Category-I daily DOTS (HRZE) by the physician. Both male and female participants equally experienced ADR during the treatment, but relatively more females (92.6%) than males (88.6%) reported ADR during Phase I. Out of 250 patients, 224 patients (89.6%) experienced one or more ADRs in Phase I. The central nervous system-related (75.6%) ADR was mostly reported followed by any gastrointestinal (74.4%), cardiovascular (49.2%) and any dermatological related (44.4%) ADRs. It is paramount to timely monitor and proactively manages ADRs pertaining to anti-TB drug treatment with minimal alteration in the treatment course.